Epigenomics: a new tool for the generation of climate resilient grapevines - Tan, Jia W.; Rodríguez López, Carlos M. (Frontiers in Horticulture, 2023)
Climate change is expected to increase the occurrence of extreme environmental conditions. Viticulture, as agriculture in general, is highly dependent on climatic conditions, not only for yield but also for fruit quality, which is the most important factor affecting produce value at the farm-gate. This demands the development of novel plant breeding techniques that will lead to the accelerated production of more resilient grape varieties, as conventional breeding programs for perennials are often prolonged. Recent research has suggested that environmental conditions can activate a memory of stress that could result in a primed response to subsequent stress events. This is a process capable of increasing plant’s resilience to abiotic stimuli, allowing plants to better adapt to extreme environmental conditions. While the effect of priming has been observed in many plants, the underlying mechanisms are puzzling and seldom studied in perennial crops. A large body of research has been developed in the last decade linking response to stress, stress priming, and memory of stress with epigenetic mechanisms. This understanding of plant epigenetics has opened the door to the application of epigenetics to crop improvement, such as the use of epigenetic breeding for the generation of more resilient crops. Perennial crop agriculture in general, and viticulture in particular, would benefit from more in-depth knowledge on epigenetic memory of stress.